Self-assembly of active attractive spheres1. Issue 21 (7th June 2015) - Prymidis, Vasileios; Sielcken, Harmen; Filion, Laura
<x xml:space="preserve">Abstract</x> We study the self-assembly of a system of self-propelled, Lennard-Jones particles using Brownian dynamics simulations.